BA ve NAA hormonları kullanılarak atalık domates bitkisinin (Solanum lycopersicum L.) in vitro mikroçoğaltımı - Karabulut, Fadime; Faızan, Mohammad; Alam, Pravej; Ali, Sajjad (Adıyaman Üniversitesi, 2025)
Bu çalışma, ata domatesin neslinin devam edebilmesi için steril koşullar altında hızlı bir şekilde çoğalmasını sağlamayı amaçlamaktadır. In vitro ortamda, domates bitkilerinin eksplantlarına farklı konsantrasyonlarda 6-Benzil Adenin (BA) ve ?-Naftalen Asetik asit (NAA) hormonlarını içeren besi ortamındaki klonal çoğaltımları araştırılmıştır. Hipokotil, kotiledon ve kotiledon boğumu eksplantları 20 günlük domates fidelerinden alınmış ve bunların BA ve NAA içeren kombinasyonları Murashige Skoog (MS) ortamında kültüre alınmıştır. Daha sonra, tüm explantlar hormonsuz MS ortamına aktarılmıştır. Araştırma sonucunda kotiledon eksplant kallus çapında en büyük artışı 0,25 BA + 0,4 NAA ppm konsantrasyonunda göstermiştir. Bu konsantrasyonu 0,50 BA + 0,8 NAA ppm konsantrasyonlarındaki iki kat artış takip etmiştir. Kallustaki sürgün sayısı önemli ölçüde kotiledon eksplantında gözlenmiş ve en çok 0,25 BA + 0,2 NAA ppm konsantrasyonunda görülmüştür. Kallus oluşumu ve gelişimi (kallus sayısı) açısından hipokotil eksplantlarında anlamlı sonuçlar bulunmuştur. Kotiledon boğumdan alınan explantlarda saksıya daha fazla ekim olduğu gözlenmiştir. Aklimatizasyon ve meyve oluşumu en fazla ata domatesin kotiledon boğumundan alınan eksplantlarda görülmüştür.

The aim of this study was to ensure the rapid reproduction of ancestral tomatoes under sterile conditions for the continuation of their generation. In vitro, clonal propagation of tomato plants was investigated on medium containing different concentrations of the hormones 6-Benzyl Adenine (BA) and ?-Naphthalene Acetic acid (NAA) in explants. Hypocotyl, cotyledon and cotyledon nodes explants were taken from 20-day-old tomato seedlings and their combinations containing BA and NAA were cultured on Murashige Skoog (MS) medium. Subsequently, all explants were transferred to hormone-free MS medium. As a result of the study, the cotyledon explant showed the greatest increase in callus diameter at a concentration of 0.25 BA + 0.4 NAA ppm. This concentration was followed by a two-fold increase at 0.50 BA + 0.8 NAA ppm concentration. The number of shoots in the callus was observed significantly in the cotyledon explant and was highest at 0.25 BA + 0.2 NAA ppm concentration. Significant results were found in hypocotyl explants regarding callus formation and development (callus number (5/5)). Explants taken from the cotyledonary node were observed to be planted more in pots. Acclimatization and fruit formation were highest in explants taken from the cotyledonary node of the ancestor tomato.
In vitro Propagation of Ancestral Tomato Plant Using 6-Benzyladenine and ?-Naphthaleneacetic Acid
Keywords: Plant Biochemistry; Bitki Biyokimyası; Plant Biotechnology; Bitki Biyoteknolojisi; Plant Physiology; Bitki Fizyolojisi; Plant Tissue and Cell Culture; Bitki Doku ve Organ Kültürü